If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10cosx + -4 = 20cosx Reorder the terms: -4 + 10cosx = 20cosx Solving -4 + 10cosx = 20cosx Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-20cosx' to each side of the equation. -4 + 10cosx + -20cosx = 20cosx + -20cosx Combine like terms: 10cosx + -20cosx = -10cosx -4 + -10cosx = 20cosx + -20cosx Combine like terms: 20cosx + -20cosx = 0 -4 + -10cosx = 0 Add '4' to each side of the equation. -4 + 4 + -10cosx = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -10cosx = 0 + 4 -10cosx = 0 + 4 Combine like terms: 0 + 4 = 4 -10cosx = 4 Divide each side by '-10osx'. c = -0.4o-1s-1x-1 Simplifying c = -0.4o-1s-1x-1
| 8m-3=-19 | | 5r=10-3r | | 2=7x-3(4x+16) | | 1/3y+11=1/2y-3 | | 30=16-2a | | 3a+5b=7b-6a | | 4a-1.6=4.8 | | 9p-8-3p+5=21 | | 6p+12=16 | | 40=6x-5(x-6) | | 30=2L+2W | | 75=3(2-6-5v) | | 39=N+N+1+N+2 | | 5x+23=54 | | 8+2y-4=9y+12-6y | | 11x-1=(3x+12)2 | | 12m+31n=-8m | | 5x+23=63 | | x^4-4x^3-64x^2-40x-4=0 | | (6*43)+(6*19)=6(43+h) | | 3n-1=(n+4)2 | | 18-16a=4a | | ln*x-ln*x^2+ln*3=0 | | 12r+24=-36 | | 2x(x-5)=4 | | bx-c=d | | 9(3-2x)=2(10-9x) | | 59(12+9)=(59*12)+(l*9) | | 3n-1=n+4 | | 0.05x+0.2(24-x)=0.1(24) | | 7(-6)+(-5)=(7*g)+(7)*(-5) | | 7x-3=9-4x |